Welfare Aspects of Estate and Gift Taxes in Life Cycle Economies - Troy Felver; 유재인 (The Korean Economic Review, 2023)
We study the welfare implications of lowering estate and gift taxes in an overlapping generations model, wherein heterogeneous agents face uncertain lifetimes and leave both accidental bequests and voluntary gifts to their children. According to the findings from the Survey of Consumer Finances, we consider inter vivos giving made by a working parent while receiving bequests from his parent(s). We conduct numerical experiments by changing tax rates and exemption levels in closed and small open economy settings. By adjusting unified tax rates, we discuss the theoretical implications of optimal gift and estate tax rates on improving aggregate capital stock and expected lifetime utility. The welfare gains from higher and broader tax rate changes are measurable and significant in a model with revenue neutrality using an alternative tax rule of capital gain taxes, thereby leading to the possibility that these taxes can effectively provide additional resources for the government to level up disadvantaged populations.
Keywords: Inter Vivos Giving; Estate and Gift Tax; Life-Cycle Model; Welfare; General Equilibrium; 증여; 유산/증여세; 생애주기모형; 복지; 일반균형